Arthroscopic Management for Bipartite Patella: A Systematic Review. Issue 8 (11th August 2021) - Loewen, Allison; Ge, Susan M.; Marwan, Yousef; Burman, Mark; Martineau, Paul A.
Background: Bipartite patella is a rare congenital condition that becomes painful following direct trauma or an overuse injury. If it remains painful despite nonoperative treatment, surgery may be warranted. The current gold standard is open fragment excision or lateral release; however, arthroscopic management is also possible. Purpose: To investigate the safety and efficacy of arthroscopic treatment of painful bipartite patella. Study Design: Systematic review; Level of evidence, 4. Methods: Using Medline and Embase, we systematically reviewed the literature as of March 8, 2020, using the subject headings "bipartite patella" and "arthroscopy" and related key terms. All levels of evidence involving human studies in English were included. Articles were excluded if only the abstract was published or the study was related to nonsurgical treatment or nonrelated diagnoses. Data related to journal/article information, demographic/clinical data, arthroscopic technique, length of follow-up, treatment outcomes, and complications were extracted. Results: Eleven articles with 43 patients were included in the review. Most patients (n = 34; 79%) underwent arthroscopic lateral release, while 16% (n = 7) had arthroscopic excision of the accessory fragment and 5% (n = 2) had arthroscopic excision and release. All patients except for one, who experienced postoperative trauma, were pain-free after arthroscopic treatment and were able to return to sports after a mean 2.6 months. Conclusion: This review demonstrated that arthroscopic management of painful bipartite patella is a safe and effective alternative to open surgical excision or release. However, all articles were case studies or small case series, owing to the rarity of the condition. In the future, higher-level studies comparing arthroscopic techniques and postoperative rehabilitation programs should be performed.